SELF MANAGEMENT DAN INVESTASI DIGITAL SEBAGAI SOLUSI MENGURANGI PRILAKU KONSUMTIF MILLENIAL MASA PANDEMI COVID-19 - Juliani Nst, Chyntia; Putri, Nurdiana; Yuherni, Yuherni (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2021)
Self-management is a technique that directs the counselee to change his behavior in a more effective direction in accordance with what he wants through the process of learning new behavior by using one strategy or a combination of several strategies. Digital investment is one example of fintech that can be felt by the wider community. This study uses a qualitative research method with a writing technique in the form of a narrative review. Writing a narrative review is a study of books, literatures, notes, and reports related to the problem to be solved. The data collection technique used in this research is documentation from secondary data sources in the form of the internet, secondary data in the form of journals, research articles, government agency reports, survey results and books. Based on the results and discussions that have been described, there has been a change in consumptive behavior during the Covid-19 pandemic. This is identified through four things, namely the purpose of consumption, influencing factors, media, and transaction tools. To reduce consumptive behavior, especially the millennial generation, by cultivating the nature of self-management and allocating income for online investment or known as digital investment.